Diversity of Vibrio spp. as pathogenic bacteria and their antimicrobial resistance profile isolated from Penaeus vannamei ponds - ROSA AMALIA; SETO WINDARTO; MADA TRIANDALA SIBERO; DION SAPUTRA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Amalia R, Windarto S, Sibero MT, Saputra D. 2024. Diversity of Vibrio spp. as pathogenic bacteria and their antimicrobial resistance profile isolated from Penaeus vannamei ponds. Biodiversitas 25: 4450-4461. Vibriosis is one of the most severe diseases affecting brackish aquaculture systems. The objective of this study was to investigate the diversity of unspeciated Vibrio spp. and antimicrobial resistance patterns of pathogenic Vibrio sp. bacteria isolated from Penaeus vannamei Boone 1931 ponds. Water and sediment samples were collected from several intensive ponds at the Marine Science Techno Park (MSTP), Universitas Diponegoro, Jepara, Indonesia. The result showed that the total vibrio count (TVC) ranged from 0.46×107 to 7.07×107 CFU mL-1 in water samples and from 4.73×107 to 20.07×107 (2.01×108) CFU mL-1 in sediment samples. In total, 150 bacterial cultures were successfully isolated. Furthermore, yellow, greenish-yellow, green, and dark green bacterial colonies were observed on the TCBS agar. Four out of the 150 isolates bacteria, T3.S.1, T1.B.1, T2.S.1, and TK.A.1 were selected based on different genetic profiles and identified by 16S rRNA sequencing. These isolates belonged to the genus Vibrio and were closely related to Vibrio alginolyticus, Photobacterium damselae, Vibrio parahaemolyticus, and Vibrio harveyi. The results of antibiotic resistance revealed that gentamicin (Cn); ampicilin (Amp); ciprofloxacin (Cip); tetracycline (Te); chloramphenicol (C); and amoxcicilin (Aml) were ineffective against V. alginolyticus, P. damselae, V. parahaemolyticus, and V. harveyi, finding indicates that these bacteria were resistant to antibiotics. Only P. damselae showed intermediate resistance to chloramphenicol (C). Further research is necessary to detect antibiotic resistance genes and virulence genes in these isolates.